Research on in vitro micropropagation of Lilium brownii F.E. Brown - Sâm, Vũ Hoài; Quỳnh, Bùi Đức; Hương, Nguyễn Thị; Khiêm, Nguyễn Văn (Vietnam Journal of Biotechnology, 2016)
Lilium brownii Brown belonging Lilium genus and Liliaceae family is well-known as a popular medicinal species, as well as food source and beautiful ornamental flowers. The specie has unique and ornamental floral characteristics such as light and elegant fragrance and perianth color rapidly changing from yellowish cream to white during anthesis. In traditional medicine, it is used for treatment cough, sedation diuretic, bronchitis... In nature, it can be found in subtropical climate moutainous areas in the North such as Sa Pa, Bat Xat, Mu Cang Chai; Sin Ho and Phong Tho, Quang Ba and Dong Van. In recent years, this species has been listed in the Red List for medicinal plants in Vietnam due to over-exploitation. The only effective strategy for sustaible conservation this species is in vitro micropropagation. In this study, in vitro plant regeneration and micropropagation of L. brownii was established from bubles and stem nodes. After surface sterilization with 0.1% HgCl2 in 10 minutes, healthy young shoots were obtained from initial bubles and stem nodes on MS medium supplemented with 0.5 mg/l BAP or 0.5 mg/l NAA, respectively. Bulblets also were formed from young shoot on MS supplemented with 0.5 mg/l NAA. The highest number of 4.5 bulblets per an explant was recorded from longitude-divided bubbles on MS medium containing 0.5 mg/l NAA and 0.2 mg/l BAP after 60 days in culture. The regererated plants produced quality roots on half strength MS supplemented with the combination of 1.0 mg/ l NAA and 0.2 mg / l BAP. More than 90% of rooted plants in vitro were survival on artificial soil TN1 in the nursery.